Enantioselective Copper‐Catalyzed Propargylic Etherification of Propargylic Esters with Phenols Promoted by Inorganic Base Additives. Issue 15 (12th July 2016) - Shao, Long; Zhang, De‐Yang; Wang, Ya‐Hui; Hu, Xiang‐Ping
Abstract: An enantioselective copper‐catalyzed propargylic etherification of both aromatic and aliphatic propargylic esters with phenols has been developed, in which the employment of inorganic base additives, in particular cesium carbonate (Cs2 CO3 ), was found to significantly promote not only the reactivity but also the enantioselectivity of the reaction. By using a structurally hindered chiral ketimine P, N, N‐ligand, a wide range of optically active propargylic ethers were prepared in high yields and with excellent enantioselectivities (up to 98% ee ). Abstract :